Influence of Incremental Impact on the Damage of Coal-Rock under Unidirectional Constraint - Hongbao Zhao; Huan Zhang; Jinyu Li; Nansong Ju; Zhijie Wen (Advances in Civil Engineering)
Taking the briquette sample as research object, the influence of the incremental impulse (momentum) on the damage of coal-rock under different uniaxial axial pressure was studied by using the self-developed pendulum impact dynamic loading test device, cooperating with the ultrasonic detection device. Meanwhile, the influence of constant impulse on the damage degree of coal-rock was compared. The results show that the damage degree of coal-rock increases with the increase of the impulse, and the damage fitting curve is upward concave, indicating that the coal sample tends to accelerating failure. Moreover, with the increase of axial pressure, the variation gradient of the damage degree of coal-rock tends to moderate and the cumulative damage degree decreases under the same impulse, and the impact resistance of coal-rock increases. When the impulse is constant, the damage degree of coal-rock increases with the number of impact, and the damage curve is upward convex, indicating that coal-rock has a tendency to slow down the damage. The cumulative damage degree of coal-rock decreases with the increase of axial pressure, and the number of impact needed to destroy coal-rock is increased. In addition, the damage model of coal-rock was proposed, and the criterion of coal-rock damage was obtained, which shows that the damage degree of coal-rock increases with the increase of impact load and decreases with the increase of static axial load.